Baseline predictors for visual acuity loss during observation in diabetic macular oedema with good baseline visual acuity. Issue 7 (1st March 2020) - Busch, Catharina; Okada, Mali; Zur, Dinah; Fraser‐Bell, Samantha; Rodríguez‐Valdés, Patricio J.; Cebeci, Zafer; Lupidi, Marco; Fung, Adrian T.; Gabrielle, Pierre‐Henry; Giancipoli, Ermete; Chaikitmongkol, Voraporn; Laíns, Inês; et al.
Abstract: Purpose: To investigate clinical baseline characteristics and optical coherence tomography biomarkers predicting visual loss during observation in eyes with diabetic macular oedema (DMO) and good baseline visual acuity (VA). Methods: A sub‐analysis of a 12‐month, retrospective study, including patients with baseline VA ≤0.1 logMAR (≥20/25 Snellen) and centre‐involving DMO. The primary outcome measure was the correlation between baseline characteristics and VA loss ≥10 letters during follow‐up. Results: A total of 249 eyes were included in the initial study, of which 147 eyes were observed and 80 eyes received anti‐vascular endothelial growth factor (VEGF) treatment at baseline. Visual acuity (VA) loss ≥10 letters occurred in 21.8% (observed cohort) and in 24.3% (treated cohort), respectively. Within observed eyes, presence of hyperreflective foci [HRF; odds ratio (OR): 3.18, p = 0.046], and disorganization of inner retina layers (DRIL; OR: 2.71, p = 0.026) were associated with a higher risk of VA loss ≥10 letters. In observed eyes with a combined presence of HRF, DRIL and ellipsoid zone (EZ) disruption, the risk of VA loss was further increased (OR: 3.86, p = 0.034). In eyes with combined presence of DRIL, HRF and EZ disruption, risk of VA loss was 46.7% (7/15 eyes) in the observed cohort, and 26.3% (5/19 eyes) in the treated cohort (p = 0.26). Conclusion: Patients with DMO and good baseline VA, managed by observation, are of increased risk for VA loss if DRIL, HRF and EZ disruption are present at baseline. Earlier treatment with anti‐VEGF in these patients may potentially decrease the risk of VA loss at 12 months.